Ergonomic Design and Development of A Seed Packing Aid for Rice Farmers - Putri, Famelga Clea; Hartomo (Jurnal Ilmiah Teknik Industri, 2025)
Rice milling is a vital agribusiness subsystem that produces rice and by-products such as seeds. UD. Sri Rejeki, a small-scale mill, still relies on manual seed packing using plates, which is repetitive, inefficient, and ergonomically risky. This study developed a vacuum-based ergonomic packing tool for rice seeds. Quality Function Deployment (QFD) identified worker needs, Rapid Upper Limb Assessment (RULA) evaluated posture, usability testing assessed tool performance, and the Mann-Whitney test compared workload before and after implementation. Design attributes were based on worker requirements, posture, and benchmarking. Usability testing showed three workers completed five tasks with a System Usability Scale (SUS) score of 70.8 (Grade C, “Good”). RULA indicated reduced posture risk from 7 (high) to 4 (low). The Mann-Whitney test confirmed a significant workload reduction after tool adoption. In conclusion, the vacuum-based ergonomic packing aid improved efficiency, reduced workload, and enhanced worker safety in small-scale rice seed packaging.